Peningkatan Kualitas Produk Celana menggunakan Metode Kaizen - Muhamad Hilman Maulana; Puti Renosori; Asep Nana Rukmana (UNISBA Press, 2024)
Abstract. PT X is a company operating in the garment industry with products such as t-shirts, trousers, shirts and jackets. The number of defective products that exceed the tolerance limit can be detrimental to the company because it has to spend more time and money to repair defective products. Improvement activities in the production process need to be carried out by companies to reduce the number of defective products by improving quality. In this research, the kaizen method is used, which is a method of continuous improvement with the participation of everyone. Based on the background that has been described, the formulation of the problem in this research is as follows: